Population and reproductive biology of a commercially important sea cucumber species, Stichopus horrens (Selenka, 1867) in Pangkor Island, Perak - Syed Mohd Khair, Syed Zulfaqar (2018)
To enhance our understanding on some of the important biological aspects of commonly targeted sea cucumber species in Malaysia, population and reproduction biology of a commercially important species of tropical sea cucumber, Stichopus horrens (Selenka, 1867) was investigated for a period of one year in Pangkor Island, Perak, Peninsular Malaysia. In total, 641 live individuals of S. horrens were collected from August 2015 to July 2016. Biometrics data were measured and population parameters were estimated using length-frequency data analyzed by FAO-ICLARM Stock Assessment Tool II (FiSAT-II) software. Reproduction was monitored through macroscopic and microscopic analyses of the gonads. The mean total weight and body length of the population was 96.80 ± 2.22 g and 15.23 ± 0.19 cm respectively. The length- weight relationship of the population was found to be W = 0.413L2.02. The growth parameter K and L∞ were estimated at 0.75 year-1 and 32.50 cm respectively. The total mortality was estimated at 2.38 year-1, natural mortality at 1.48 year-1 and fishing mortality at 0.90 year-1. The level of exploitation was at 0.38 and below the optimum level of 0.50. The gonad weight and tubule diameter were significantly different between male and female, being heavier and longer in the latter. The gonad index peaked at 0.76% in September, 2015 and gradually declined to the lowest at 0.03% in May, 2016 which was also proportional to the changes in tubule diameters. Histological examination of gonads revealed that the highest proportion of mature individuals was in September, 2015 when the spawning started and prolonged up to April, 2016 with the majority spawned in October, 2015. The size-class distribution of oocyte showed the dominant distribution of large mature oocytes (80–100 μm) from October to December 2015. The size at first sexual maturity was estimated at 20 cm in length and 135 g in total weight. The mean absolute fecundity was 1,100,727 (± 148,613 SE) and significant positive relationship between fecundity and size of the individuals was found. The population parameters revealed that this species is a relatively fast grower with high mortality. The findings also suggested that spawning of S. horrens might be seasonal with major spawning occurring from October to January. The results also demonstrated that spawning took place over a long period of time and mature species can be found almost throughout the year. The species also reaches late sexual maturity and the reproductive viability increase with increasing size and also probably ages. The prolonged release of gametes and availability of matured adults throughout the year might facilitate sustainable aquaculture program of this species. The period of enhanced spawning observed will also contribute to better management of broodstocks in such program to a greater extent.